Serum Sodium Level on the Recurrence of Febrile Seizure within the Same Febrile Illness-Experience in a District Level Hospital (TAJ: Journal of Teachers Association, 2019)
Introduction: Febrile convulsion is the most common seizure disorder in the pediatric age group. It occurs in 2-5% of children. A febrile seizure is a seizure accompanied by fever (temperature 100.4°F or 38°C by any method), without central nervous system infection, that occurs in infants and children 6 through 60 months of age.Aim: The study was conducted to see the effect of serum sodium level on the recurrence of febrile seizure during the same febrile illness. Materials and Method: A cross-sectional descriptive study which enrolled 65 children admitted with febrile seizures at 100 bed district hospital, Naogaon. They were divided in to two groups, those with a single seizure and the rest were children with more than one seizures. Serum sodium levels were estimated after stabilization of patients. The probability of recurrent febrile seizures and serum sodium level was analyzed.Results: Hyponatremia (serum sodium